2013
DOI: 10.1371/journal.pone.0080612
|View full text |Cite
|
Sign up to set email alerts
|

Diets High in Heat-Treated Soybean Meal Reduce the Histamine-Induced Epithelial Response in the Colon of Weaned Piglets and Increase Epithelial Catabolism of Histamine

Abstract: We examined the influence of dietary fermentable protein (fCP) and fermentable carbohydrates (fCHO) on the colonic epithelial response to histamine in pigs. Thirty-two weaned piglets were fed 4 diets in a 2 × 2 factorial design with low fCP/low fCHO, low fCP/high fCHO, high fCP/low fCHO and high fCP/high fCHO. After 21-23 days, the pigs were killed and tissue from the proximal colon was stimulated with carbachol, histamine, PGE2 or sodium hydrogen sulphide in Ussing chambers. Changes in short-circuit current a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Interestingly, diets high in fermentable protein reduced the activity of the large intestinal epithelial ameloride-sensitive sodium channel ENaC, which was associated with more liquid feces in piglets (Richter et al, 2014). Indirect effects of protein-derived metabolites include higher formation of histamine, which contribute to increased chloride secretion and fluid loss into the large intestinal lumen through receptor-mediated signaling (Kröger et al, 2013(Kröger et al, , 2015. Other factors such as digesta viscosity or digesta transit may promote the ability of enterobacteria to adhere to specific mucus motifs in the small intestine.…”
Section: The Role Of Protein Fermentation In Diarrhea In Pigsmentioning
confidence: 99%
“…Interestingly, diets high in fermentable protein reduced the activity of the large intestinal epithelial ameloride-sensitive sodium channel ENaC, which was associated with more liquid feces in piglets (Richter et al, 2014). Indirect effects of protein-derived metabolites include higher formation of histamine, which contribute to increased chloride secretion and fluid loss into the large intestinal lumen through receptor-mediated signaling (Kröger et al, 2013(Kröger et al, , 2015. Other factors such as digesta viscosity or digesta transit may promote the ability of enterobacteria to adhere to specific mucus motifs in the small intestine.…”
Section: The Role Of Protein Fermentation In Diarrhea In Pigsmentioning
confidence: 99%
“…On the one hand, the enzyme-coding genes HNMT and APN were upregulated in the jejunum. Kröger et al [32] reported that high dietary inclusion of fermentable CP increased the HNMT expression in the colon, which is a histamine-degrading enzyme. They determined that the histamine catabolism activity of HNMT counter-regulated the increased production of this biogenic amine, reducing the fecal score of the piglets fed with a high fermentable CP diet.…”
Section: Discussionmentioning
confidence: 99%
“…A list of 56 genes related to intestinal health were selected according to the bibliography [19][20][21][22][23][24][25][26][27][28][29][30][31][32] and included: (1) genes participating in the barrier function (OCLN, ZO1, CLDN1, CLDN4, CLDN15, MUC2, MUC13 and TFF3); (2) genes that play an important role in the immune response, such as pattern recognition receptors, cytokines, chemokines and stress proteins (TLR2, TLR4, IL1B, IL6, IL8, IL10, IL17A, IL22, IFNG, TNF, TGFB1, CCL20, CXCL2, IFNGR1, HSPB1, HSPA4, REG3G, PPARGC1A, FAXDC2 and GBP1);…”
Section: Open Array Designmentioning
confidence: 99%
“…A list of 56 genes related to intestinal health were selected according to the bibliography [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] and included: (1) genes participating in the barrier function ( OCLN , ZO1 , CLDN1 , CLDN4 , CLDN15 , MUC2 , MUC13 and TFF3 ); (2) genes that play an important role in the immune response, such as pattern recognition receptors, cytokines, chemokines and stress proteins ( TLR2 , TLR4 , IL1B , IL6 , IL8 , IL10 , IL17A , IL22 , IFNG , TNF , TGFB1 , CCL20 , CXCL2 , IFNGR1 , HSPB1 , HSPA4 , REG3G , PPARGC1A , FAXDC2 and GBP1 ); (3) genes coding for enzymes and hormones implicated in the digestion process ( GPX2 , SOD2 , ALPI , SI , DAO1 , HNMT , APN , IDO1 , GCG , CCK , IGF1R and PYY ); (4) genes involved in nutrient transport ( SLC5A1 , SLC16A1 , SLC7A8 , SLC15A1 , SLC13A1 , SLC11A2 , MT1A , SLC30A1 and SLC39A4 ); (5) genes involved in stress response ( CRHR1 , NR3C1 and HSD11B1 ); and (6) four reference genes ( ACTB , B2M , GAPDH and TBP ).…”
Section: Methodsmentioning
confidence: 99%